Pengaruh Kepemimpinan Visioner, Kewirausahaan, dan Kemampuan Manajerial terhadap Implementasi Strategi Bisnis serta Dampaknya pada Kinerja Perusahaan Industri Garmen Jawa Barat - Nana Robinson (Kontigensi : Jurnal Ilmiah Manajemen, 2017)
The aim of this research is to know, review and analyze: (1) Visionary Leadership, Entrepreneurship,Managerial Capability, Business Strategy Implementation, and Corporate Performance, (2) The influence ofVisionary Leadership, Entrepreneurship, and Managerial Capability toward Business Strategy Implementation,(3) The influence of Business Strategy Implementation to Corporate Performance. Research method which used is descriptive and verificative, technique sampling used is proportionatecluster random sampling with sample size is 88 respondents. Data analysis method used is path analysis. The result of this research shows that: (1).Visionary Leadership is good enough, (2). Entrepreneurship isgood enough, (3). Managerial Capability is good enough, (4). Business Strategy Implementation is goodenough, (5). Corporate Performance is good enough, (6).The influence of Visionary Leadership,Entrepreneurship and Managerial Capability to Business Strategy Implementation are significant, (7) theinfluence of Business Strategy Implementation to Corporate Performance is significant.